2010
DOI: 10.1016/j.ssc.2010.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of multiferroic order in hexagonal ceramics

Abstract: We have investigated the effects of substituting In for Mn on the antiferromagnetic phase transition in YMnO 3 using magnetic, dielectric, and specific heat measurements. We prepared a set of isostructural phase pure hexagonal YMn 1-x In x O 3 samples having x=0 to x=0.9, which exhibit a systematic decrease of the antiferromagnetic ordering temperature with increasing In content. The multiferroic phase, which develops below T N , appears to be completely suppressed for x≥0.5 in the temperature range investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…The sharp slope change is consistent with earlier reports for single crystals [144][145][146]. However, the magnetic signature at may be less clear in powder samples, possibly due to sample quality or grain size problems [43,90,95,[147][148][149][150].…”
Section: Magnetoelectric Effects In Hexagonal Manganitessupporting
confidence: 91%
“…The sharp slope change is consistent with earlier reports for single crystals [144][145][146]. However, the magnetic signature at may be less clear in powder samples, possibly due to sample quality or grain size problems [43,90,95,[147][148][149][150].…”
Section: Magnetoelectric Effects In Hexagonal Manganitessupporting
confidence: 91%
“…Recently, Yoo et al [28] have also observed the SG phase in Cr-doped h-YMnO 3 and it was found that the transition temperature increases with Cr-doping due to double exchange interaction between Cr 3 þ and Mn 3 þ ions. However, it has also been observed that replacing Mn by non-magnetic In suppresses the magnetic ordering without introducing any new phase transitions below T N [29]. A spin-glass like freezing has been observed in γ-Fe 2 O 3 [30] and CoFe 2 O 4 [10] nanoparticles ( $ 3 nm), which was attributed to the collective blocking and localized spin canting in the low temperature regime.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in multiferroic manganites ReMnO 3 (Re = Gd  Lu, Y) remains rather high 1–7. The search of new materials is directed toward finding compounds with higher magnetic ordering temperature and stronger magnetoelectric coupling.…”
Section: Introductionmentioning
confidence: 99%